archaeological investigations in san Pedro, chachapoyas, Peru - Ruiz Estrada, Arturo (2013)
We present the results of the scans in the archaeological complex of San Pedro de Utac in the province of Chachapoyas, to know the nature of the site, the architectural features and other cultural elements that characterize it as part of the ancient pre-Hispanic cities in the area